Real-time computed tomography fluoroscopy-guided dye marking prior to robotic pulmonary resection - Yoko Yamamoto; Naoki Ikeda; Masahisa Nakamura (Journal of Cardiothoracic Surgery)
Abstract Background The detection of tumor localization is difficult in robotic surgery because surgeons have no sense of touch and rely on visual information. This study aimed to evaluate the efficacy of preoperative CT-guided dye marking of lung nodules prior to robotic surgery. Methods Patients undergoing CT-guided dye marking prior to robotic surgery at our hospital between September 2019 and April 2024 were retrospectively analyzed. Results Thirty lung nodules from 29 patients were analyzed. The dye marking procedure was successfully completed. Indigo carmine and indocyanine green were used for 20 and 10 pulmonary nodules, respectively. Slight pneumothorax was the most common complication and occurred in 6 patients (20.7%), none of whom required chest tube placement. Dye marking was visualized in 29/30 (96.7%) nodules and one nodule had poor intraoperative visualization due to severe adhesions. One patient underwent open thoracotomy because of difficulty ventilating one lung. Fourteen patients underwent wide wedge resection and 16 patients underwent segmentectomy for the target nodules. All target nodules were successfully resected with negative margins. Conclusions CT-guided dye marking of small pulmonary nodules prior to robotic surgery appears feasible and safe. This procedure can facilitate the performance of robotic sublobar resection.